Social Media Marketing and Brand Image: The Mediating Role of Brand Trust on Purchase Intention among Generation Z - Indriasari, Dewi Pratiwi (Amkop Management Accounting Review (AMAR), 2025)
This study aims to examine the influence of social media marketing and brand image on purchase intention through the mediating role of brand trust among Generation Z consumers. In the digital era, Generation Z represents a dominant consumer segment that is highly engaged with social media platforms and brand-related content. However, the effectiveness of social media marketing and brand image in shaping purchase intention remains inconsistent without considering psychological factors such as trust. This research employs a quantitative approach using a survey method. Data were collected from Generation Z respondents in Bandung through structured questionnaires measured on a five-point Likert scale. The analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test both direct and indirect relationships among variables. The findings indicate that social media marketing and brand image significantly influence brand trust, which in turn significantly affects purchase intention. Furthermore, brand trust plays a mediating role in strengthening the relationship between marketing activities and consumers’ purchase intention. This study contributes to marketing literature by emphasizing the strategic importance of trust-building in digital marketing strategies targeting Generation Z.